Education and Training of Civil Servants at the Staffing and Human Resource Development Agency of East Bolaang Mongondow Regency - Zidane Haryoyudanto,; Evi Elvira Masengi,; Steven Tarore, (Technium Social Sciences Journal, 2025)
This study aims to describe, analyze and interpret the effectiveness of the implementation of education and training of civil servants and the inhibiting and supporting factors at the Personnel and Human Resources Development Agency of East Bolaang Mongondow Regency. This research uses qualitative research methods. The existing research results show that: 1) Implementation of Technical Education and Training for Civil Servants; the Technical Education and Training agenda for civil servants in a year has been planned about 2-3 times by BKPSDM Boltim Regency. However, technical training activities have not been effectively carried out from 2022 to 2024. Because of the lack of budget and even the absence of training facilities and training presenters or Widiyaiswara. 2) Implementation of Structural Education and Training for Civil Servants; the form of Structural Education and Training activities for civil servants in BKPSDM Boltim Regency is Leadership Training. However, only 2 officials have participated in Leadership Training out of 5 (five) officials who have Structural Positions who are entitled to take Structural Training. So that the implementation of Structural Training is still not optimal and not in accordance with the established agenda. The inhibiting and supporting factors in this study are Human Resources, Budget, and even Facilities and Infrastructure.